INFLUENCE OF LAND COVER IN PERMANENT PRESERVATION AREAS ON FLOOD EVENTS DOWNSTREAM OF A DAM: PEDRA FURADA HPP CASE STUDY – PERNAMBUCO, BRAZIL - Pereira, Ludmilla Freitas [UNESP]; Lima, César Gustavo da Rocha [UNESP]; Tashima, Mauro Mitsucchi [UNESP] (UNESP - Universidade Estadual Paulista, 2022)
The present study aimed to analyze the effects of soil cover in Permanent Preservation Areas (PPAs) downstream of the HPP Pedra Furada Dam, in Sirinhaem river in Brazil (Ribeirão-PE), in the occurrence of flows for return periods of 10 and 10,000 years. Field survey data such as orthophotos, topography and bathymetric information were used provided by the company that owns the dam, also public hydrological data from the National Water Agency (Agência Nacional de Águas-ANA). Through the simulation of the two-dimensional hydrodynamic model with the software HEC-RAS 5.0.7, in transient regime, the roughness coefficients (Manning) of the margins of Sirinhaém River were varied, making analyzes in distant sections 5, 15 and 25 km from the dam. The results showed that the occupation of these PPAs by native/tree vegetation increased the roughness coefficient. At best, it provided an 8-fold increase of this coefficient, reducing the time of arrival of the wave in 2h50 min for the scenario of 10-year flood and in 2h10min for the scenario of 10,000-year flood in the most distant section of the dam. For the nearest section, this increase in Manning’s value led to an increase in water depth of, approximately, 2 meters inside the river channel, for both flow scenarios. Therefore, it is concluded that well-vegetated PPAs reduce the height of the water depth over flood plains closer to the dam, in addition to delaying the wave's arrival in more distant points, contributing to the implementation of contingency in case of emergency.
INFLUÊNCIA DA COBERTURA DO SOLO EM ÁREAS DE PRESERVAÇÃO PERMANENTE SOBRE EVENTOS DE INUNDAÇÕES A JUSANTE DE UMA BARRAGEM: ESTUDO DE CASO DA PCH PEDRA FURADA – PERNAMBUCO, BRASIL
Keywords: Dams; Flood; HEC-RAS; Land Cover; Manning roughness coefficient